Job Satisfaction among Librarians in Tirunelveli District - Balasubramanian, P. (Journal of Information and Knowledge, 2011)
Job satisfaction refers to an individual’s complex reaction towards his job. It seems eminently logical that a happy employee is a better employee. Librarians are the indispensable corner stone of the society. This article studies about job satisfaction of library professionals. The study concludes that job satisfaction of an employee is related to an individual’s expectations and attainment of their perceptions.